Characteristic analysis of convective systems and their circulation background with different lifetime during meiyu period(梅雨期不同生命史对流系统及其环流背景特征分析) - 刘瑞(LIU Rui); 朱佩君(ZHU Peijun); 张红蕾(ZHANG Honglei) (Zhejiang Daxue xuebao. Lixue ban, 2025)
Based on ISCCP path tracking dataset during the meiyu period from 1998 to 2007, statistics and factors were measured on the long and short lifetime convective system (CS) in Zhejiang province and its surrounding areas, and the water vapor conditions, thermal and dynamic characteristics of the synthesized field were analyzed. It was found that more than 70% of the CS originating in the study area still affected the region. The initial moment of CS with short lifetime has obvious diurnal variation, and the intensity of CS with long lifetime is stronger. CS form distributed northeast-southwest due to strong west and southwest winds. The water vapor transport conditions of long and short lifetime CS are consistent and stable, and the water vapor transport from South China Sea and Western Pacific is obvious. The thermal conditions of short lifetime CSs are more prominent and the local characteristics are obvious. The dynamic drive is more significant in long lifetime CSs. The cyclonic shear in the lower troposphere is combined with the strong divergence center and obvious vertical shear brought by the upper jet stream, and the CSs can be maintained for a long time.基于国际卫星云气候计划（ISCCP）路径追踪数据集，根据生命史长短进行分类，对浙江省及周边区域1998—2007年梅雨期对流系统（convective system，CS）进行特征统计和环境要素场合成分析。研究发现，在起源于研究区域的CS中70%以上依然影响该区域。短生命史CS初始时刻日变化明显，而长生命史CS相对偏强。CS形态呈东北-西南走向，主要受盛行环境风影响。根据合成的水汽条件、热力和动力特征，发现长、短生命史CS的水汽输送路径较一致，主要来自南海和西太平洋，其中长生命史CS的水汽条件相对有利；短生命史CS的环境热力不稳定条件相对突出，且局地特征明显；长生命史CS的动力特征更显著，对流层低层气旋式切变配合高空急流带来的强辐散中心，以及明显的垂直风切变共同促使CS长时间维持。